Pathologic Response Rates of Gemcitabine/Cisplatin versus Methotrexate/Vinblastine/Adriamycin/Cisplatin Neoadjuvant Chemotherapy for Muscle Invasive Urothelial Bladder Cancer. (8th December 2013) - Lee, Franklin C.; Harris, William; Cheng, Heather H.; Shenoi, Jaideep; Zhao, Song; Wang, Junfeng; Champion, Thomas; Izard, Jason; Gore, John L.; Porter, Michael; Yu, Evan Y.; Wright, Jonathan L.
Abstract : Objectives . To compare pathologic outcomes after treatment with gemcitabine and cisplatin (GC) versus methotrexate, vinblastine, adriamycin, and cisplatin (MVAC) in the neoadjuvant setting. Methods . Data was retrospectively collected on 178 patients with T2-T4 bladder cancer who underwent radical cystectomy between 2003 and 2011. Outcomes of interest included those with complete response (pT0) and any response (≤pT1). Odds ratios were calculated using multivariate logistic regression. Results . Compared to those who did not receive neoadjuvant chemotherapy, there were more patients with complete response (28% versus 9%, OR 3.11 (95% CI: 1.45–6.64), P = 0.03 ) and any response (52% versus 25%, OR 3.23 (95% CI: 1.21–8.64), P = 0.01 ). Seventy-two patients received GC (n = 41 ) or MVAC (n = 31 ). CR was achieved in 29% and 22% of GC and MVAC patients, respectively (multivariate OR 0.39, 95% CI 0.10–1.58). Any response (≤pT1) was achieved in 56% of GC and 45% of MVAC patients (multivariate OR 0.45, 95% CI 0.12–1.71). Conclusions . We observed similar pathologic response rates for GC and MVAC neoadjuvant chemotherapy in this cohort of patients with muscle invasive urothelial cancer (MIBC). Our findings support the use of GC as an alternative regimen in the neoadjuvant setting.